Results from a Meta-analysis of Combination of PD-1/PD-L1 and CTLA-4 Inhibitors in Malignant Cancer Patients: Does PD-L1 Matter? - Feng, Yuqian; Jin, Huimin; Guo, Kaibo; Xiang, Yuying; Zhang, Yiting; Du, Wurong; Shen, Minhe; Ruan, Shanming (Frontiers in Pharmacology, 2021)
Background: Combination therapy with immune checkpoint inhibitors (ICIs) has been widely used for clinical treatment in recent years, which has a better survival benefit. However, not all patients can derive clinical benefit from combination immunotherapy. Therefore, it is necessary to explore the biomarkers of combination immunotherapy. Methods: We retrieved articles from electronic databases including PubMed, EMBASE and Cochrane. The statistical analysis was performed using RevMan software. Progression free survival (PFS), overall survival (OS) and objective response rate (ORR) were the outcome indicators. In the unselect population, we compared combination therapy with other treatments. In addition, we also conducted subgroup analysis on PFS, OS and ORR according to PD-L1 status. Results: Seven studies were included in the analysis for a total of 3,515 cases. In the unselected population, we found that combination therapy has longer PFS, OS, and better ORR than other treatments for cancer patients. The longer PFS was showed in PD-L1≥5% cases (HR = 0.64, 95% CI: 0.56–0.76; p < 0.001) than PD-L1 ≥1% cases (HR = 0.72, 95% CI: 0.66–0.79; p < 0.001), while ORR and OS have not related to the status of PD-L1. Conclusion: This study supported the efficacy of combination therapy with immune checkpoint inhibitors (ICIs), and also showed that PFS in patients with malignant tumors is positively correlated with PD-L1 expression. Due to the limited number of trials included, more high-quality clinical randomized controlled trials should be conducted to confirm the review findings.